Primulina hengshanensis (Gesneriaceae), a new species from Danxia landform in Hunan, China - Tian, Jing; Liu, Lei; Xiao, Shun-Yong; Zhu, Xiao-Wen; Wu, Yao-Jing; Zhou, Liu; Yin, Juan; Pen, Ling; Cai, Xiu-Zhen; Liu, Lin-Han; Liu, Ying-Di; Liu, Ke-Ming (Phytotaxa, 2018)
Primulina hengshanensis, a new species of Gesneriaceae from the Danxia formation in Hunan Province, China, is described and illustrated. The new species is similar to P. langshanica, but has numerous diagnostic features that are outlined. It conservation status is assessed as VU (vulnerable) following IUCN criteria.